A small group intervention for older primary school-aged low-progress readers: Further evidence for efficacy. (21st December 2019) - Wheldall, Kevin; Bell, Nicola; Wheldall, Robyn; Madelaine, Alison; Reynolds, Meree; Arakelian, Sarah
Abstract: The aim of the present study was to determine the efficacy of a small-group reading instruction program that was delivered over two school terms to Australian students in Years 3 through 6. A large cohort ( n = 239) of primary school children was assessed on their literacy skills before and after receiving 'MacqLit', a phonics-based program designed for older struggling readers. Parametric and nonparametric difference tests were used to compare results at pre- and postintervention time points. Statistically significant improvements with large effect sizes were observed on all raw score measures of word reading, nonword reading, passage reading and spelling. Statistically significant improvements were also observed on standard score measures of nonword reading and passage reading, suggesting the gains were greater than what might be expected to have resulted from typical classroom instruction. The results indicate that older middle primary school-aged students may benefit from phonics-based, small-group reading instruction.